Diversity and Morphometry of Chiropteran Fauna in Jahangirnagar University Campus, Savar, Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2016)
The study was conducted to know the diversity of Chiropterans as well as their status and morphometric measurements in Jahangirnagar University campus between July, 2014 and April, 2015. Eight species of bats from three families were identified where Common Pipistrelle (Pipistrellus pipistrellus) and Pouch Tomb Bat (Saccolaimus saccolaimus) were recorded for the first time in Bangladesh. A total of 31bat individuals of 8 species were captured during 15 netting nights for morphological studies. Skull preparation was carried out for taking cranial measurements to identify the Pipistrelle species. No roosting colony of Pteropus gigantius was found in the study area but it visits the area only for foraging while the other species roost permanently. The old buildings in the study area provide suitable habitats for a significant number of insectivore bats. Indian Flying Fox (Pteropus gigantius) was the largest (mean head body length 23.33±1.86cm) and Least Pipistrelle (Pipistrellus tenuis) was the smallest (mean head body length 39.45±1.66 mm) species observed from the study area.Bangladesh J. Zool. 43(2): 201-212, 2015